Heavy metal contamination of groundwater due to fly ash disposal of coal-fired thermal power plant, Parichha, Jhansi, India. Issue 1 (31st December 2016) - Verma, Chanchal; Madan, Sangeeta; Hussain, Athar
Abstract: The present study focused on the groundwater contamination due to fly ash disposal of coal-fired thermal power plant into a non liner ash pond. Six villages were selected as study site around ash pond of Parichha thermal power plant, Jhansi. Groundwater samples were collected on seasonal basis; winter season (January 2015), pre monsoon season (May 2015), and monsoon season (August 2015) using composite sampling method. Five heavy metals (Pb, Ni, Cr, Mn, and Fe) were detected in coal, fly ash, and groundwater samples. Heavy metal concentration in coal and fly ash was assessed by Energy Dispersive X-ray Fluorescence, while AAS was used for groundwater assessment. Heavy metal concentration in groundwater was ranged as Pb (0.170–0.581 ppm), Ni (0.024–0.087 ppm), Fe (0.186–11.98 ppm), Cr (0.036–0.061 ppm), and Mn (0.013–0.178 ppm). The observed results revealed the exceeding value of heavy metals prescribed by WHO for groundwater.